Pelaksanaan Pembuktian Tindak Pidana Narkotika LP/A/57/V/2026/SPKT.SATRESNARKOBA/POLRESINHIL/POLDA RIAU Tanggal 29 Mei 2026 - Gideon Brilyan Tito Nababan Hukum; Vivi Arfiani Siregar; Kms Novyar Satriawan F (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2026)
This study aims to analyze the implementation of evidentiary procedures in narcotics crime cases under Case Number LP/A/57/V/2026/SPKT.SATRES NARKOBA/POLRES INHIL/POLDA RIAU dated May 29, 2026, and to identify the obstacles encountered by investigators along with the efforts undertaken to overcome them. This research employs an empirical legal method with a descriptive-analytical nature using normative juridical and empirical juridical approaches. Data were collected through interviews, observation, and literature study, then analyzed qualitatively using a deductive method. The findings indicate that the evidentiary process was conducted in accordance with the Indonesian Criminal Procedure Code and Law Number 35 of 2009 on Narcotics through the collection of lawful evidence, including witness testimony, expert testimony, documentary evidence, physical evidence, and suspect statements. The main obstacles include limited human resources, inadequate supporting facilities, inter-agency coordination, and other external factors. Investigators addressed these obstacles by strengthening coordination, enhancing professionalism, and improving the completeness of investigation administration.